Exposure to American Football and Neuropsychiatric Health in Former National Football League Players: Findings From the Football Players Health Study. Issue 12 (October 2019) - Roberts, Andrea L.; Pascual-Leone, Alvaro; Speizer, Frank E.; Zafonte, Ross D.; Baggish, Aaron L.; Taylor, Herman; Nadler, Lee M.; Courtney, Theodore K.; Connor, Ann; Grashow, Rachel; Stillman, Alexandra M.; Marengi, Dean A.; et al.
Background: Former American football players have a higher prevalence of cognitive impairment than that of the US general population. It remains unknown what aspects of playing football are associated with neuropsychiatric outcomes. Hypothesis: It was hypothesized that seasons of professional football, playing position, and experience of concussions were associated with cognition-related quality of life (QOL) and indicators of depression and anxiety. Study Design: Descriptive epidemiology study. Methods: The authors examined whether seasons of professional football, playing position, and experience of concussions, as measured by self-report of 10 symptoms, were associated with cognition-related QOL and indicators of depression and anxiety in a cross-sectional survey conducted 2015 to 2017. Cognition-related QOL was measured by the short form of the Quality of Life in Neurological Disorders: Applied Cognition–General Concerns. The Patient Health Questionnaire–4 measured depression and anxiety symptoms. Of 13, 720 eligible men with apparently valid contact information, 3506 players returned a questionnaire at the time of this analysis (response rate = 25.6%). Results: Seasons of professional play (risk ratio [RR] per 5 seasons = 1.19, 95% CI = 1.06-1.34) and playing position were associated with cognition-related QOL. Each 5 seasons of play was associated with 9% increased risk of indicators of depression at borderline statistical significance ( P = .05). When compared with former kickers, punters, and quarterbacks, men who played any other position had a higher risk of poor cognition-related QOL, depression, and anxiety. Concussion symptoms were strongly associated with poor cognition-related QOL (highest concussion quartile, RR = 22.3, P < .001), depression (highest quartile, RR = 6.0, P < .0001), and anxiety (highest quartile, RR = 6.4, P < .0001), even 20 years after last professional play. Conclusion: The data suggest that seasons of play and playing position in the NFL are associated with lasting neuropsychiatric health deficits. Additionally, poor cognition-related QOL, depression, and anxiety appear to be associated with concussion in the long term.